SUFISM OF LIBERATION: REREADING THE CONCEPT OF FEMALE CREATION AND GENDER-BASED VIOLENCE ISSUES - Umi Ni'matin Choiriyah (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2025)
This paper discusses the concept of the creation of women from a Sufi perspective as an effort to prevent gender-based violence. The focus of this study is the concept of the creation of women from a Sufi perspective to understand the role and function of women from the beginning of their creation as an effort to prevent violence against women. The research was conducted using qualitative methods. Data analysis was carried out by thoroughly analyzing Sufi literature that discusses the creation of women. The results of the study show that in Sufism, women were created from nafs wahidah, which is the same self as men. From nafs wahidah, they were then divided into two parts, male and female. Thus, Sufism views them as having the same roles, positions, and rights as caliphs on Earth, because Allah sees humans based on their piety, not their gender. They were created to complement and understand each other in order to achieve a complete life and harmonious relationships as preparation for carrying out their role as caliphs on Earth. As for the roles of men and women that cannot be interchanged, these are roles related to their biological conditions, such as childbirth and breastfeeding Keywords: Sufism Liberation, Female Creation, Gender Violence